2023
DOI: 10.3390/nu15112523
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition-Based Strategies to Reduce Exercise-Induced Muscle Damage and Soreness

Abstract: Exercise induced-muscle damage (EIMD) occurs after strenuous and/or novel exercise that involves repeated eccentric contractions [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In the context of post-activity, and even following sports-related trauma or muscle injuries, it has been suggested that Astragalus supplementation might potentially expedite athletes' recuperation [34]. In a trial with eleven male participants receiving astragalosides supplementation (4 mg per day for a week) or placebo pills, the intervention effectively reduced biomarkers associated with muscle damage and inhibited the secretion of proinflammatory cytokines (IL-6 and TNF-α), while simultaneously increasing the release of the muscle regenerative factor IGF-1 during the initial phases of the recovery process [35].…”
Section: Purported Mechanism Of Actionmentioning
confidence: 99%
“…In the context of post-activity, and even following sports-related trauma or muscle injuries, it has been suggested that Astragalus supplementation might potentially expedite athletes' recuperation [34]. In a trial with eleven male participants receiving astragalosides supplementation (4 mg per day for a week) or placebo pills, the intervention effectively reduced biomarkers associated with muscle damage and inhibited the secretion of proinflammatory cytokines (IL-6 and TNF-α), while simultaneously increasing the release of the muscle regenerative factor IGF-1 during the initial phases of the recovery process [35].…”
Section: Purported Mechanism Of Actionmentioning
confidence: 99%
“…Intensifying training effectiveness hinges on injury prevention and expediting the recovery process, which plays a pivotal role in harnessing the body's adaptive response to exercise stress (Impellizzeri et al, 2020). Consequently, after intense physical exertion, individuals may encounter exercise-induced muscle damage, a phenomenon commonly recognized as delayed-onset muscle soreness (DOMS) (Barnes, 2023;Setiawan et al, 2022). DOMS, characterized by muscle discomfort or pain, is frequently associated with various forms of muscle contractions, including isometric, concentric, eccentric, or combinations thereof (Mautner & Sussman, 2016;Ruas et al, 2022).…”
Section: Introductionmentioning
confidence: 99%